2015
DOI: 10.1227/neu.0000000000000623
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Feasibility Study on Robotic Endonasal Telesurgery

Abstract: Background Novel robots have recently been developed specifically for endonasal surgery. They can deliver several thin, tentacle-like surgical instruments through a single nostril. Among the many potential advantages of such a robotic system is the prospect of telesurgery over long distances. Objective To describe a phantom pituitary tumor removal done by a surgeon in Nashville, Tennessee, controlling a robot located approximately 800 km away in Chapel Hill, North Carolina. This is the first remote telesurge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 30 publications
0
39
0
Order By: Relevance
“…The new developed instrumentations include high definition 3D endoscopic system, (31) endoscopic augmented reality navigation system, (32) ultrasonographyassisted endoscope, (33) the indocyanine green fluorescence endoscope, (34) and use of highfield intraoperative MRI, (35) et al These are reported to increase the safety and reduce the risk of the endoscopic approach (Table 3). Recently, an experimental feasibility study on (36). 4K (and 8K) ultra-high definition endoscopes are likely to be introduced to this field in the near future (14).…”
Section: Future Advancesmentioning
confidence: 99%
“…The new developed instrumentations include high definition 3D endoscopic system, (31) endoscopic augmented reality navigation system, (32) ultrasonographyassisted endoscope, (33) the indocyanine green fluorescence endoscope, (34) and use of highfield intraoperative MRI, (35) et al These are reported to increase the safety and reduce the risk of the endoscopic approach (Table 3). Recently, an experimental feasibility study on (36). 4K (and 8K) ultra-high definition endoscopes are likely to be introduced to this field in the near future (14).…”
Section: Future Advancesmentioning
confidence: 99%
“…It offers neurosurgeons a minimally invasive surgical technique for procedures in the cranial base in which specific surgical instruments and an endoscope are inserted through the patient's nostrils. This procedure is known as EEA (endoscopic endonasal approach) [22]- [24]. Fig.1 shows the focus of an EEA procedure.…”
Section: Neurosurgerymentioning
confidence: 99%
“…Several clinical teams have performed surgical operations with access to the base of the skull through the nasal fossa [22][23][24] and [49] using Intuitive Surgical's commercial system, Da Vinci: a generalpurpose teleoperated surgical robotic system. Several advantages are described in works with this robot.…”
Section: Robotics In the Neurosurgery Fieldmentioning
confidence: 99%
“…"Telesurgery" has since been an active area of technological research and development. Recent trials have attempted to assess the effect of communication latency on surgical performance [22][23][24], expand the scope of procedures achievable through telesurgery [24,25] and improve haptic feedback relayed to remote operators [26]. However, at present, telesurgery requires acquisition and maintenance of a robotic platform that is likely to be prohibitively expensive for rural treatment sites [27].…”
Section: Surgery and Postoperative Carementioning
confidence: 99%